Wanita Karir dan Dampaknya terhadap Rumah Tangga - Norma, Asmanol; Jazuli, Muhammad; Halimah, Siti; Niswah, Hilyatun; Efendy, Noor (Sharia Journal and Education Center Publishing, 2024)
Abstract This research aims to determine the dual role of women and women’s motivation to become career women and to determine the impact of women’s dual role in maintaining family harmony. This research is field research. Data collection was carried out using observation, interviews and documentation methods. This research analyzed the data using data reduction, data presentation and verification. The results of the research show that strategies for maintaining family harmony in women’s careers are (1) how career women balance their time between taking care of the household and work (2) the role of husbands in helping with housework while women are working (3) differences in views from the surrounding community regarding career women and ordinary housewife women (4) differences in taking care of the household before and after becoming a career woman (5) How career women educate their children in the midst of busy work. 6) The impact of career women in taking care of the household Keywords: Career Woman, Family, Impact Abstrak Penelitian ini bertujuan untuk mengetahui peran ganda perempuan serta motivasi perempuan untuk menjadi wanita karir dan untuk mengetahui dampak dari peran ganda perempuan dalam menjaga menjaga keharmonisan keluarga. Penelitian ini merupakan penelitian lapangan (field research). Pengumpulan data dilakukan dengan metode observasi, wawancara dan dokumentasi. Penelitian ini di analisis data menggunakan reduksi data, penyajian data dan verification. Hasil penelitian menunjukkan bahwa strategi menjaga kerukunan keluarga dalam karir wanita adalah (1) cara wanita karir menyeimbangkan waktu antara mengurus rumah tangga dengan pekerjaan (2) peran suami saat membantu pekerjaan rumah disaat wanita sedang bekerja (3)perbedaan pandangan dari masyarakat sekitar mengenai wanita karir dan wanita irt biasa (4) perbedaan dalam mengurus rumah tangga sebelum dan sesudah menjadi wanita karir (5) Cara wanita karir mendidik anak ditengah kesibukan pekerjaan. 6) Dampak Wanita karir dalam mengurus rumah tangga Kata Kunci: Wanita Karir, Keluarga, Dampak